2022
DOI: 10.3390/jcm11123469
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Outcome Following Stent-Assisted Coiling for Wide-Necked Aneurysms Using Three Different Stent Models: A Single-Center Experience

Abstract: Previous case series have described the safety and efficacy of different stent models for stent-assisted aneurysm coiling (SAC), but comparative analyses of procedural results are limited. This study investigates the procedural outcome and safety of three different stent models (Atlas™, LEO+™ (Baby) and Enterprise™) in the setting of elective SAC treated at a tertiary neuro-endovascular center. We retrospectively reviewed all consecutively treated patients that received endovascular SAC for intracranial aneury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This paper is the first to study four types of stents (Solitaire ™ , Enterprise ™ , LVIS(JR) ™ , LEO+(Baby) ™ ) simultaneously. Previous studies on the effects of Atlas ™ , Enterprise ™ , and LEO ™ stents on angiographic outcomes after SAC of wide-neck aneurysms showed a high incidence of total occlusion at long-term follow-up [29]. No significant difference was similarly observed among different stents, and the results of this research coincided with this finding.…”
Section: Discussionsupporting
confidence: 86%
“…This paper is the first to study four types of stents (Solitaire ™ , Enterprise ™ , LVIS(JR) ™ , LEO+(Baby) ™ ) simultaneously. Previous studies on the effects of Atlas ™ , Enterprise ™ , and LEO ™ stents on angiographic outcomes after SAC of wide-neck aneurysms showed a high incidence of total occlusion at long-term follow-up [29]. No significant difference was similarly observed among different stents, and the results of this research coincided with this finding.…”
Section: Discussionsupporting
confidence: 86%
“…Several recent reports evaluating angiographic outcomes and safety in unruptured cases treated with SAC showed no difference when stratified by stent model. 10 , 11) …”
Section: Stent-assisted Coilingmentioning
confidence: 99%
“…Several recent reports evaluating angiographic outcomes and safety in unruptured cases treated with SAC showednodifferencewhenstratifiedbystentmodel. 10,11) In a report on unruptured middle cerebral artery aneurysms,SACsignificantlyreducedtherecurrenceratecompared to simple coiling without increasing the risk of complications. 12) Although SAC has clearly improved the treatment of wide-neck aneurysms, it is not indicated for casesofacuteruptureanditsuseisoff-label.Adecadeago, a review reported a higher complication rate after acute SAC thanwithoutstenting.Recently,itwas reportedthat Neuroform Atlas may be suitable for acutely ruptured aneurysms owing to its low-profile design and reduced metal construction.…”
Section: Stent-assisted Coilingmentioning
confidence: 99%
“…The Enterprise stent (Codman, Raynham, MA) was the second one to receive US FDA approval for stent-assisted coiling and the first one with a closed-cell design. It has now become a well-established tool for treatment of aneurysm and intracranial atherosclerotic stenosis as an off-label application ( 9 16 ). The second-generation Enterprise stent is a further development with a changed closed-cell design of the strut geometry to improve its adherence to the vascular wall, especially in curved arteries ( 10 ).…”
Section: Introductionmentioning
confidence: 99%